Stress‐assisted formation of surface gratings on polymer films. Issue 7 (29th November 2012) - Lin, Chiao‐Chi; Yang, Fuqian; Chin, Joannie W.; Sung, Lipiin; Lee, Sanboh
Abstract The effect of biaxial‐residual–compressive surface stress on the surface modulation of solid films is analyzed. The results show that the biaxial compressive stress can create surface modulation with the orientation being 45° (135°) to the principal directions of the stresses. Using uniaxial tension, a complementary set of nonsymmetrical polymer ripple gratings is formed on the fracture surface of a polymer film that is sandwiched between two relatively glass slides. The effect of geometrical shape and boundary confinement is examined on the surface modulation. The orientation of the polymer ripple gratings is found to be 45° to the longitudinal direction of the films for long‐rectangular polymer thin films in accord with the analysis. POLYM. ENG. SCI., 2013. © 2012 Society of Plastics Engineers